The construction works of elevated water tank at Taman Abad, Tebrau, Johor / Nurul Aimi Ajlaa Md.Hasrin - Md.Hasrin, Nurul Aimi Ajlaa (Universiti Teknologi MARA UiTM,Perak, 2022)
Elevated water storage tank is a raised structure supporting a water tank built or constructed at a height adequate to compress an appropriation framework for consumable water, and to give crisis stockpiling to fire assurance. Water storage tank regularly work related to underground or surface service reservoirs, which store treated water near where it will be utilized. The objective of this report is to learn how to build a good elevated water storage tank that fulfil the requirements needed based on Suruhanjaya Perkhidmatan Air Negara (SPAN) and any related requirements from Ranhill SAJ Johor. Last but not least is to acknowledge the difference between the ground water storage tank and elevated storage tank and methodology in building the structures. While building this elevated water storage tank there is so many methods that has being used in order to finish this project. One of them is they need to consider every element to construct this project. To conclude, this project is a very important to every section of industries specially to house residential area as water demand or supply is one of a must elements that need in every day